Effect of stannous chloride combined with caffeine on fecundity of Drosophila prosaltans - Itoyama, Mary Massumi [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP] (FapUNIFESP (SciELO), 2000)
The present study analyzed the number of progeny of stannous chloride- and/or caffeine-treated Drosophila prosaltans. A significant decreasing effect was observed in every case when compared to the control, except for the smallest stannous chloride dose used. Combinations of both substances using two different stannous chloride doses did not differ significantly from each other but number of progeny decreased 15% with the higher concentration combination when compared with caffeine-treated flies. The present results and data in the literature indicate that the effects of continuous ingestion of stannous chloride should be studied.
Keywords: caffeine; stannous chloride; Drosophila; fertility; Drosophila prosaltans